Un ensayo sobre la evolución de l Geografía Urbana en España: reinventar el estudio de la ciudad - Precedo Ledo, Andrés (Geographicalia, 2014)
This paper is a critical essay on the evolution of urban geography studies in Spain. The long teaching, researching and professional author’s experience is the basis of a speech, supporting the original aims to provide a new point of equilibrium for urban studies between the theoretical and methodological advances and the instrumental techniques. This discussion provides a summary of the innovations process of urban geography from 1970 to 1990 and suggests a new conceptual framework to the urban geographical studies inside a valorisation process to design in the new international urban system from a humanistic and social perspective.
Keywords: urban geography; geographic method; urban philosophy; urban positioning; reinvention urban studies; globalization.